2007
DOI: 10.1080/10428190701493910
|View full text |Cite
|
Sign up to set email alerts
|

The use of hypomethylating agents in the treatment of hematologic malignancies

Abstract: Epigenetic alterations, such as DNA methylation and histone modifications, are abnormal in cancer cells, and the use of the hypomethylating agents 5-azacitidine and decitabine are important additions to our arsenal of active cancer drugs, especially for the treatment of the myelodysplastic syndromes and acute myeloid leukemia. Most effective are repeated cycles of the drugs given at doses much lower than originally tested. Typical overall response rates (complete responses + partial responses + hematologic imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…About epigenetic therapeutic strategy the DNA demethylation agent combined with HDI have been shown to produce synergistic reactivation of anti-tumor effects to yield promising results in clinical studies (Kihslinger et al, 2007). Both quercetin and butyrate themselves exhibited combined effectiveness of demethylation and HDI in anti-human esophageal cancer 9706 cells.…”
Section: Discussionmentioning
confidence: 99%
“…About epigenetic therapeutic strategy the DNA demethylation agent combined with HDI have been shown to produce synergistic reactivation of anti-tumor effects to yield promising results in clinical studies (Kihslinger et al, 2007). Both quercetin and butyrate themselves exhibited combined effectiveness of demethylation and HDI in anti-human esophageal cancer 9706 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the possibility that the mechanistic functions of azacitidine may be multifactorial. [29][30][31] Previous studies have shown the DNA methylation decrease with azacitidine treatment, though one must also entertain the possibility that DNA methylation reduction serves as a pharmacodynamic rather than a therapeutic marker. Up to 90% of azacitidine is incorporated into mRNA, while the deoxyribonucleoside structure in another DNMT inhibitor, 5-aza-2'-deoxycytidine (decitabine), leads to complete DNA incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Classical DNMT inhibitors (DNMTi's), including decitabine and azacitidine, can induce significant clinical responses and even prolong the survival of patients with higher-risk myelodysplastic syndrome 16,17 and are being actively investigated in other myeloid malignances. 18 These studies raise the possibility that DNMTi's might be useful in tumors with active DNA replication, such as DLBCL; however, the optimal dose schedule for these agents remains to be fully clarified.…”
Section: Non-hodgkin Lymphomas Ii: Breakthroughs In Treatment Of Highmentioning
confidence: 99%